Analysis on carrageenan content of seaweed Kappaphycus Alvarezii at different water condition in Bantaeng District. Issue 1 (October 2021) - Asni, A.; Najamuddin,
Abstract: Seaweed Kappaphycus alvarezii has high carrageenan content and highly use as a main ingredient in food industry, cosmetics, pharmacy and organic fertilizer. The research aimed to analyze the seaweed carrageenan content at different water conditions, locations and cultivation distance from coast line. The research conducted in Bantaeng district coastal water during. Experimental method applied and interview with seaweed farmer and also laboratory examination. Each station consists of 3 substations (distance from coast line, near, middle and far) in triplicate. Environmental parameters measured biweekly during 45 days' cultivation periods per season. Samples collected and seaweed weight for carrageenan content analysis conducted at the beginning and at the end of experiment. Univariate analysis of variance applied to analyze the effects of seasons, locations and distance toward seaweed carrageenan content. Result of the study showed that seasons and distance were significantly (P<0.05) affect the seaweed carrageenan content. Carrageenan content were range 44.77 – 63.96%, fulfill the national standard of Ministry of Trade for 25 % as well as the international standard 40%. Carrageenan content were higher during rainy season at cultivation distance 1500 m from the coast line (P<0.05). Carrageenan content was highly correlated with sea current speed and phosphate content during rainy season while salinity and turbidity during dry season.